(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Staphylococcus aureus is the most frequently encountered pathogen isolated from clinical specimens. Prolonged hospitalization, indiscriminate use of antibiotics, and indwelling medical devices were the cause for the appearance and spread of methicillin resistant staphylococcus aureus (MRSA). MRSA strains have a high effect on patient morbidity and mortality. Material and methods: A total of 208 Methicillin resistance staphylococcus aureus isolates were taken from various clinical samples and processed in accordance with standard protocol. Results: In this research, among 601 staphylococcus aureus isolates, 393 (65.40%) were MSSA and 208 (34.60%) were MRSA. Analysis of clindamycin Resistance in 208 MRSA isolates showed 19.7% of inducible clindamycin Resistance. Conclusion: The pattern of clindamycin resistance to MRSA varies in different regions. When clindamycin is considered for therapy, the kind of resistance (inducible or constitutive clindamycin resistance) which exists to be detected. ‘D test’ is absolutely necessary in microbiology laboratories. This is because it avoids misinterpretation of clindamycin resistance byclearly delineating inducible clindamycin resistance from constitutive clindamycin resistance.